2014
DOI: 10.1063/1.4851255
|View full text |Cite
|
Sign up to set email alerts
|

The transverse field Richtmyer-Meshkov instability in magnetohydrodynamics

Abstract: In ideal magnetohydrodynamics MHD, the Richtmyer-Meshkov instability can be suppressed by the presence of a magnetic field. The interface still undergoes some growth, but this is bounded for a finite magnetic field. A model for this flow has been developed by considering the stability of an impulsively accelerated, sinusoidally perturbed density interface in the presence of a magnetic field that is parallel to the acceleration. This was accomplished by analytically solving the linearized initial value problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 25 publications
6
52
0
Order By: Relevance
“…The verifications tests include: linear wave propagation tests, regular shock refraction at a density interface in MHD (this example is truly a multidimensional verification of the solution in the neighborhood of shock refraction and described in thorough detail in Wheatley et al 25 ), and magnetic reconnection. 23 Furthermore, convergence tests in a variety of contexts have been presented in Wheatley et al 17,26 For completeness, we present the equations and numerical method below.…”
Section: A Numerical Methodsmentioning
confidence: 99%
“…The verifications tests include: linear wave propagation tests, regular shock refraction at a density interface in MHD (this example is truly a multidimensional verification of the solution in the neighborhood of shock refraction and described in thorough detail in Wheatley et al 25 ), and magnetic reconnection. 23 Furthermore, convergence tests in a variety of contexts have been presented in Wheatley et al 17,26 For completeness, we present the equations and numerical method below.…”
Section: A Numerical Methodsmentioning
confidence: 99%
“…13 Samtaney 14 showed that growth of the MHD RMI is suppressed under a magnetic field normal to the material interface in certain planar flow configurations and Wheatley et al [15][16][17] subsequently investigated the mechanism of this suppression. Further research also examined the suppression of the RMI by transverse 18,19 and oblique 20 seed fields for planar MHD flows. Characterizing the dynamics of MHD implosions under the effect of seed fields would assist in a fundamental investigation of the MHD RMI in cylindrical or spherical converging flows, to complement the literature [21][22][23][24] on its hydrodynamic counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…These equations are already expressed in non-dimensional form by choosing a reference density, pressure, and length scale (for example, see Wheatley et al 12 for the non-dimensionalization). F(U), G(U), and H(U) are the fluxes of mass, momentum, magnetic flux, and energy in the r, θ, and z directions given as…”
Section: B Governing Equationsmentioning
confidence: 99%
“…In these MHD investigations, the initial seed magnetic field was parallel to the incident shock front. Wheatley et al 12 investigated the case where the magnetic field was parallel to the interface, i.e., there was no normal component of the magnetic field at the interface, and found oscillatory solutions with the RMI still being suppressed. In these prior MHD investigations of RMI, the geometry was planar.…”
Section: Introductionmentioning
confidence: 99%